MAPLE AND MATHCAD PROGRAMMING METHODS FOR SOLVING MATH PROBLEMS - Zaurebekov Н.C; Bodyk А.М (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The article discusses the features of teaching computer science and mathematics in secondary schools based on interdisciplinary communication. Integration of mathematics and computer science contributes to the algorithmic thinking of students in the process of solving logical, textual, arithmetic, geometric problems. The main didactic task of interdisciplinary communication is to establish a connection between the educational, educational, developing nature of the educational process. The use of computer programs to solve problems related to mathematics, the use of computers to accelerate student learning and teaching them to work independently. His interest in the subject is growing, his talent and personal abilities are developing, as well as the quality of teaching, the speed of the educational process is increasing.